Truncated hantavirus nucleocapsid proteins for serotyping Sin Nombre, Andes, and Laguna Negra hantavirus infections in humans and rodents - Koma, Takaaki (2010)
Fil: Koma, Takaaki. Department of Microbiology, Graduate School of Medicine, Hokkaido University; Japón.